NILAI-NILAI PENDIDIKAN KARAKTER DALAM CERPEN KORAN HARIAN SINGGALANG PERIODE JANUARI-APRIL 2019 - Hamdani, Syahrul; Gani, Erizal (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2019)
ABSTRACT This study aims to (1) describe the values of character education contained, (2) describe the values of character education that often appear in, (3) describe character education values which rarely appears, and (4) describes the values of character education that are not in the short stories of the Singgalang Daily newspaper. The method used in this research is descriptive method. Based on the results of the study, the values of character education studied in the short story of the Singgalang Daily newspaper were found. First, the short stories contained in the Singgalang Daily newspaper contain eighteen values of character education, namely the value of religious character education, honesty, tolerance, discipline, hard work, creative, democratic, independent, curiosity, national spirit, love for the country , appreciates achievement, is friendly/communicative, loves peace, likes to read, cares about the environment, cares for the social, and takes responsibility. Second, the value of character education that often arises is the value of friendly/ communicative character education. Third, character education values that rarely emerge are the spirit of nationalism, love of peace, and love to read. Kata kunci: nilai, pendidikan karakter, cerpen, koran, Harian Singgalang